Consumer Protection in E-commerce Transactions in Indonesia: A Case Study of Fraud in Online Purchases - Pangesti, Trias; Prastyanti, Rina Arum (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The rapid growth of e-commerce in Indonesia provides convenience in conducting transactions, but also increases risks for consumers, especially regarding online fraud such as unrealized delivery of goods or unreal sellers. The purpose of this study is to evaluate how effective legal protection is for consumers who are victims of fraud in electronic transactions. The method used in this research is normative juridical with a case study approach to examine existing regulations and their implementation in the field. The research findings show that legal protection for consumers in Indonesia has been regulated through Law No. 8/1999 on Consumer Protection and Law No. 11/2008 on Electronic Information and Transactions, but its implementation still faces various challenges, such as weak control, difficulty in proving the identity of the perpetrator, and the low level of digital literacy of the community. The case studies analyzed show that legal measures taken against e-commerce fraud often do not provide adequate resolution for victims. Therefore, there is a need to strengthen regulations, improve monitoring mechanisms for e-commerce platforms, and provide education to consumers to reduce the risk of fraud in online transactions.